FAKTOR-FAKTOR YANG MEMENGARUHI STRUKTUR MODAL - Marhendra, Marhendra; Viriany, Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research aims to obtains empirical evidences on the influence of profitability, likuidity, toward capital structure. This research uses secondary data which was tested with Eviews version 9. The data that is used in this research coming from manufacturing companies automotive and components that are listed in the Indonesian Stock Exchange during year 2019-2021, in which with purposive sampling method there are 12 companies chosen as samples. The results of this research are that profitability has a significant positive effect on the capital structure that is rejected, and liquidity has a significant effect on the capital structure that is accepted.